ANALISIS MINAT SISWA TERHADAP MATA PELAJARAN FISIKA DI PONPES AL- MUKHLISHIN SIBUHUAN - Parinduri, Sri Handayani; Nurjannah, Siti (Institut Agama Islam Negeri Padangsidimpuan, 2024)
The purpose of this study was to determine students' interest in physics subjects from the results of the description of the attitudes of Ponpes Al-Mukhlishin Sibuhuan students. This type of research is quantitative using survey research procedures with the instrument used is a questionnaire. The subjects of this study were 50 students of Ponpes Al-Mukhlishin Sibuhuan. The results showed that the learning interest of Ponpes Al-Mukhlishin Sibuhuan students in class X Science 1, X Science 2 in physics subjects was good although there are some students whose interest in learning is still lacking. In order for students' interest in learning to have better and more increased physics lessons, teachers must use more innovative approaches, and models and use more interesting media so that students are interested in following learning.